Treatment of Morbidly Adherent Placentation Utilizing a Standardized Multidisciplinary Approach in the Community Hospital-Private Practice Setting - Mahsa Mansouri; Kim DeStefano; Brian Monks; Jasbir Singh; Mollie McDonnold; Jamison Morgan; Richard Hale; Jasvant Adusumalli; Amanda Horton; Sina Haeri (Thieme Medical Publishers, Inc., 2017)
Abstract Objective Morbidly adherent placentation is associated with increased maternal morbidity and mortality. Recently, there has been mounting evidence supporting the benefits of a standardized multidisciplinary approach at tertiary teaching hospitals. Our objective was to estimate the impact of the implementation of a similar program at a high-volume private community hospital. Study Design In this retrospective cohort study, we evaluated maternal outcomes in all cases of histopathologically confirmed morbidly adherent placentation since the initiation of our multidisciplinary program (2012-2016). Our data were compared with the previously published outcomes of two large cohorts from tertiary teaching hospitals in Utah and Texas. Results In the 28 cases included for evaluation, our group's median estimated blood loss, median packed red blood cells transfused, median anesthesia time, median length of stay, or rates of maternal morbidity did not statistically differ from the published data in Utah or Texas. Conclusion Our data demonstrate the feasibility and utility of a multidisciplinary morbidly adherent placentation program in the private practice/community hospital setting with outcomes similar to those at tertiary teaching hospitals. Implementation of such program may prove beneficial in remote centers, where various factors may prohibit patient travel to a larger center.